Orexin-1 receptor blockade dysregulates REM sleep in the presence of orexin-2 receptor antagonism - Dugovic, Christine; Shelton, Jonathan E.; Yun, Sujin; Bonaventure, Pascal; Shireman, Brock T.; Lovenberg, Timothy W. (Frontiers in Neuroscience, 2014)
In accordance with the prominent role of orexins in the maintenance of wakefulness via activation of orexin-1 (OX1R) and orexin-2 (OX2R) receptors, various dual OX1/2R antagonists have been shown to promote sleep in animals and humans. While selective blockade of OX2R seems to be sufficient to initiate and prolong sleep, the beneficial effect of additional inhibition of OX1R remains controversial. The relative contribution of OX1R and OX2R to the sleep effects induced by a dual OX1/2R antagonist was further investigated in the rat, and specifically on rapid eye movement (REM) sleep since a deficiency of the orexin system is associated with narcolepsy/cataplexy based on clinical and pre-clinical data. As expected, the dual OX1/2R antagonist SB-649868 was effective in promoting non-REM (NREM) and REM sleep following oral dosing (10 and 30 mg/kg) at the onset of the dark phase. However, a disruption of REM sleep was evidenced by a more pronounced reduction in the onset of REM as compared to NREM sleep, a marked enhancement of the REM/total sleep ratio, and the occurrence of a few episodes of direct wake to REM sleep transitions (REM intrusion). When administered subcutaneously, the OX2R antagonist JNJ-10397049 (10 mg/kg) increased NREM duration whereas the OX1R antagonist GSK-1059865 (10 mg/kg) did not alter sleep. REM sleep was not affected either by OX2R or OX1R blockade alone, but administration of the OX1R antagonist in combination with the OX2R antagonist induced a significant reduction in REM sleep latency and an increase in REM sleep duration at the expense of the time spent in NREM sleep. These results indicate that additional blockade of OX1R to OX2R antagonism elicits a dysregulation of REM sleep by shifting the balance in favor of REM sleep at the expense of NREM sleep that may increase the risk of adverse events. Translation of this hypothesis remains to be tested in the clinic.